Characterization of electrical properties of different chemical sprays for electrostatic spraying - JYOTI, BIKRAM; MANI, INDRA; KUMAR, ADARSH; KHURA, TAPAN K (The Indian Journal of Agricultural Sciences, 2019)
Application of chemicals application of chemical is an essential component of agriculture production system. Excessive use of these chemicals has led to search for a suitable chemical application method. Electrostatic spraying can be a viable option to eradicate the existing problem in chemical application. Electrical properties of spray liquid play an important role to impart charge to the spray droplet and it subsequent transportation to the intended target. Therefore it is necessary to characterize the spray liquid in terms of electrical properties for selected chemicals and their concentrations for electrostatic spraying. Hence, the present study was conducted to analyze the spray liquids in terms of their electrical properties using different chemicals. The implications of each electrical property with respect to spray chargeability, deposition on to the target, biological efficacy and suitability for electrostatic charging were established. The electrical conductivity varied from 0.50-0.526, 531-565 and 497-546 μs/cm for distilled, ground and tap water, respectively at all selected levels of concentration and chemicals. For ground water and tap water, both the electrical conductivity was significantly higher than that of distilled water. Dielectric constant varied from 80.18–80.28, 80.26–80.42 and 80.597–80.66 for distilled, ground and tap water, respectively at all selected levels of concentration and chemicals. For ground water and tap water, the dielectric constant was higher than that of distilled water.